Management of Instructional Document Archives for Arabic Language Learning in Madrasah: Pengelolaan Arsip Pengajaran Bahasa Arab di Madrasah - Faliqul Isbah; Moh Nurul Huda; Sukma Zuliana; Muhammad Rifai (Language Development Center, 2025)
Background: The management of instructional document archives for Arabic language learning in madrasahs plays a crucial role in supporting the effectiveness of instructional management and improving the quality of education. However, various instructional documents such as lesson plans, modules, teaching materials, evaluation instruments, and learning outcome reports are often not systematically documented, which creates difficulties for teachers and madrasah administrators in planning, implementing, and evaluating the teaching process. Purpose: This article aims to examine the urgency of implementing archival management of Arabic language instructional documents in madrasahs and to propose solutions based on modern archival principles to ensure more effective, efficient, and sustainable document management. Method: This study employs a descriptive-analytical approach, highlighting the current practices of instructional document archival management in madrasahs and analyzing them within the framework of educational archival management principles. Results and Discussion: A structured management system for Arabic language instructional document archives can enhance accountability, improve instructional management, and contribute to the overall quality of education in madrasahs. The implication is that madrasahs should adopt archival systems based on modern principles, both physical and digital, to support teacher professionalism and the sustainability of the learning process. Conclusions and Implications: The findings reveal that weak archival management in madrasahs leads to disorganized instructional documents, limited accessibility, and potential loss of important records. The application of modern archival principles is shown to better organize instructional documents, facilitate easier access, and ensure both security and sustainability.